Bilateral ankle deformities affects gait kinematics in chronic stroke patients - Kim, Hogene; Cho, Ji-Eun; Seo, Kyeong-Jun; Lee, Jooyoung (Frontiers in Neurology, 2023)
Objectives Stroke patients suffer from ankle joint deformities due to spastic ankle muscles. This study evaluated the viability of using 3D scanned surface images of the feet of stroke victims to visually assess the deformities of a hemiparetic foot and investigated the influences of deformed ankle joints on gait kinematics. Methods A total of 30 subjects with stroke-induced hemiparesis and 11 age-matched healthy controls completed the clinical assessments. We analyzed their feet's morphometric characteristics using a 3D scanner, identified convenient anthropometric measurements, and conducted gait trials on even and uneven terrains. The 3D foot morphometric characteristics were evaluated using the geometric morphometrics method (GMM). Results Results showed that there were significant differences in bilateral foot shapes between the chronic stroke patients and healthy controls and between the paretic and non-paretic sides in the chronic stroke patients. In stroke patients, those with the smaller medial malleoli's vertical tilt angles showed significantly different ankle ranges of motion of dorsi-/plantar flexion during gaits on uneven terrains (p = 0.009). In addition, those with the greater medial malleoli's vertical tilt angles showed significantly different ankle ranges of motion of inversion/eversion during gaits on even and uneven terrains (p < 0.05). Conclusion Using 3D scanning technology, bilateral morphometric changes in the feet of chronic stroke patients were shown by GMM and the simple anthropometric measurements identified its shape deformities in the feet. Their possible effects on gait kinematics while walking on uneven terrains were investigated. Current methodology can be potentially useful in applying conventional productions of clinically manufactured, patient-fitted ankle-foot-orthosis in orthotics and prosthetics, and in detecting various unidentified pathological deformities in the feet.